2012
DOI: 10.1097/tp.0b013e318272df41
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Transmission From Organ Donors—Unavoidable But Low Risk

Abstract: DTC is rare but frequently results in graft loss and death. The risk of cancer transmission cannot be eliminated because, in every case, the presence of cancer was not known at donation. This information will allow informed consent for prospective recipients. Explantation/excision is likely to benefit recipients with localized cancer, but in transplants other than kidney/pancreas, the benefits should be balanced against the risks of retransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
127
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 18 publications
0
127
0
Order By: Relevance
“…Transplanting a solid organ carries an unavoidable, but low risk of transmitting an infectious or neoplastic disease from donor to recipient (82). The risk of donor transmitted malignancies should be weight against the urgency to receive a transplant graft.…”
Section: Secondary Lung Cancer In the Allograftmentioning
confidence: 99%
“…Transplanting a solid organ carries an unavoidable, but low risk of transmitting an infectious or neoplastic disease from donor to recipient (82). The risk of donor transmitted malignancies should be weight against the urgency to receive a transplant graft.…”
Section: Secondary Lung Cancer In the Allograftmentioning
confidence: 99%
“…Donors with central nervous system malignancies should be carefully evaluated as certain risk factors are associated with malignancy transmission; organs from donors having high grade (Ⅲ or Ⅳ) tumors, ventriculo-systemic shunts or history of extensive cranial surgery that disrupts the blood-brain barrier are associated with a transmission rate of 45% and should not be considered for transplantation; in cases where the underlying etiology of brain death is unclear, a rapid limited brain autopsy should be conducted [37] . Data derived from the United Kingdom Transplant Registry showed that 18 solid organ recipients developed cancer from 16 donors (0.06%): 3 were donor-derived cancer (0.01%) and 15 were donor-transmitted cancer (0.05%) [38] . Of the 15 donor-transmitted cancers, 6 were renal; 5 were lung; 2 were lymphoma; 1 was neuroendocrine, and 1 colon cancer [38] .…”
Section: Malignanciesmentioning
confidence: 99%
“…Data derived from the United Kingdom Transplant Registry showed that 18 solid organ recipients developed cancer from 16 donors (0.06%): 3 were donor-derived cancer (0.01%) and 15 were donor-transmitted cancer (0.05%) [38] . Of the 15 donor-transmitted cancers, 6 were renal; 5 were lung; 2 were lymphoma; 1 was neuroendocrine, and 1 colon cancer [38] . Some recent Italian series have shown no disease transmission with use of grafts from donors with lowgrade malignancies or neoplasms of low metastatic potential [39,40] .…”
Section: Malignanciesmentioning
confidence: 99%
“…In 1999, the United Network for Organ Sharing (UNOS) Transplant Tumor Registry began to examine donor malignancy data and in their recent report of donor data between 2000 to 2005 four deaths from donor transmitted malignancies were identified [10]. The reported risk of donor tumor transmission rates have ranged from 0.01% [11] to 0.05% [12].…”
mentioning
confidence: 99%